A Meta-Analysis of Functional Communication Training Effects on Problem Behavior and Alternative Communicative Responses. (December 2018) - Chezan, Laura C.; Wolfe, Katie; Drasgow, Erik
We conducted a meta-analysis of single-case research design (SCRD) studies on functional communication training (FCT). First, we used the What Works Clearinghouse (WWC) Standards to evaluate each study. Next, we calculated effect sizes using Tau-U. Then, we aggregated the effect sizes across the studies to produce an omnibus effect size. Results indicate that more than half of the SCRD studies met the WWC Standards and that FCT was effective in decreasing the level of problem behavior and in increasing the level of the alternative communicative response (ACR), but effectiveness varied according to such factors as type of disability and age. Furthermore, the results of visual analysis corresponded with Tau-U effect sizes in more than half of the cases. Implications for researchers and practitioners are discussed.